CORPORATE VOLUNTEERING AS AN ELEMENT OF SUSTAINABLE DEVELOPMENT OF THE ORGANIZATION - Natalia Ivanovna Gorlova (Science and Innovation Center Publishing House, 2018)
Purpose. The article is devoted to the topic of development of corporate volunteering, which is topical for Russian society. The subject of the analysis is corporate volunteering in Russia and its impact on the sustainable development of the organization. Corporate volunteering is seen at the intersection of the interests of the company, employees and the local community. The aim of the research is a theoretical analysis of modern practices of corporate volunteer activity as a factor of sustainable development of the organization.